El mito de la capacidad contributiva: Breves comentarios sobre la regulación actual del Impuesto a la Renta de Personas Naturales y una propuesta a futuro - Meneses Morales, Indhira (2015)
This paper aims at analyzing the current regulation of the income Tax of Individuals from a critical point of view of its effects on taxpayers’ ability to pay. Also, it propose a different solution to the current model of taxation in our country, which is found more accordance with the wealth of the taxpayers.